EFFECTS OF RACISM ON PEOPLE IN VULNERABLE CONTEXTS AND WITH ALCOHOL AND DRUG USE - Marcelino, Miguel dos Santos; Alves, Stefania Vallado; Surjus, Luciana Togni de Lima e Silva (Seven Editora, 2025)
This study investigated the effects of racism on the lives of people experiencing social vulnerability and using alcohol and other drugs, based on interventions carried out within the DiV3rso extension project. Using a qualitative approach, the research employed collective activities, an anonymous mural, group discussions, and short interviews to understand how structural inequalities, racial discrimination, and social suffering shape patterns of drug use and participants’ life trajectories. The findings revealed that racism—both explicit and subtle—produces psychological, emotional, and social impacts that manifest in drug use, whether as a way of coping with pain, seeking belonging, or responding to experiences of exclusion. The practices developed within the DiV3rso project, aligned with harm reduction principles, enabled support, affective exchange, and the reconstruction of social bonds, approaching a liberating praxis inspired by Fanon. The study concludes that comprehensive care requires recognizing the role of structural racism in deepening vulnerabilities and promoting spaces of sensitive listening and mutual recognition, which are essential for strengthening autonomy, dignity, and care in freedom. DOI: https://doi.org/10.56238/sevened2025.037-052